Treatment of hereditary hypotrichosis simplex of the scalp with topical gentamicin. (1st July 2020) - Peled, A.; Samuelov, L.; Sarig, O.; Bochner, R.; Malki, L.; Pavlovsky, M.; Pichinuk, E.; Weil, M.; Sprecher, E.
Summary: Background: Hypotrichosis simplex of the scalp (HSS) is characterized by progressive loss of scalp hair that results in almost complete baldness at a young age. HSS is often caused by dominant nonsense mutations in CDSN encoding corneodesmosin, leading to the formation of an amyloid‐like material, which interferes with normal hair follicle cycle. Objectives: As gentamicin has been shown to mediate ribosomal read‐through, we aimed to ascertain its therapeutic efficacy in a small series of patients carrying a recurrent mutation in CDSN . Methods: We used a green fluorescence reporter assay system, confocal microscopy and Western blot analysis to ascertain in vitro the ability of gentamicin to induce translational read‐through across a causative CDSN mutation. Results: Using a reporter assay, we initially showed that gentamicin induces read‐through activity across an HSS‐causing nonsense mutation. Gentamicin was further shown to rescue corneodesmosin translation in primary keratinocytes obtained from a patient with HSS. To validate the in vitro data, we conducted a pilot clinical trial where the scalp of four patients was treated topically with gentamicin for 6 months, demonstrating significant improvement as ascertained by the Severity of Alopecia Tool score. Conclusions: Our findings indicate that topical gentamicin should be considered as a potential therapeutic modality in HSS. What's already known about this topic? Hypotrichosis simplex of the scalp (HSS) is caused by nonsense mutations in CDSN encoding corneodesmosin. The mutant corneodesmosin has been hypothesized to be toxic to the hair follicles, leading to hypotrichosis. Disorders caused by nonsense mutations are amenable to ribosomal read‐through using gentamicin. What does this study add? Gentamicin enhanced read‐through activity and promoted full‐length corneodesmosin synthesis in primary keratinocytes derived from patients carrying a nonsense mutation in CDSN . Topical treatment with gentamicin was found to rescue the hypotrichosis phenotype partially in four patients with HSS. What is the translational message? Topical gentamicin should be considered as a potential treatment for HSS. Linked Comment: Kibbi and Rajan. Br J Dermatol 2020; 183 :11 .